Pengaruh Pembelajaran Aktif, Inovatif, Kreatif, Efektif Dan Menyenangkan (PAIKEM) Oleh Guru Pendidikan Agama Kristen Terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 3 Lintongnihuta Tahun Pembelajaran 2023/2024 - Sonita Jola Angleny Simatupang; Betty A.S Pakpahan; Robert K.A Simangunsong; Adiani Hulu; Baginda Sitompul (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The aim of this research is to determine the positive and significant influence of Active, Innovative, Creative, Effective and Fun Learning (PAIKEM) by Christian Religious Education teachers on the Learning Interest of Class VIII Students at SMP Negeri 3 Lintongnihuta for the 2023/2024 Academic Year. The research method used is a descriptive quantitative method. The population is all students in class VIII of SMP Negeri 3 Lintongnihuta, Humbang Hasundutan Regency for the 2023/2024 academic year who are Protestant Christians, totaling 177 students and a sample of 43 people was determined using the Random Sampling technique. Data was collected using a closed questionnaire with 35 items, namely 17 items for variable Learning Interests of Class VIII Students at SMP Negeri 3 Lintongnihuta for the 2023/2024 Academic Year. 1) The results of data analysis show: a) a positive relationship test obtained a value of rxy = 0.612 > rtable(=0.05,n=43) = 0.375. b) Testing a significant relationship obtained tcount= 4.961 > ttable(=0.05, dk=n-2=41)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂="10.29"+0.84X. b) Regression coefficient of determination test (r2) = 37.5%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=21, dk denominator=n-2=43-2=41) namely 24.61 > 1.51. Thus Ha is accepted and H0 is rejected.